Effect of smoking on pleural thickening in asbestos workers. Issue 10 (October 1993) - Yano, E; Tanaka, K; Funaki, M; Maeda, K; Matsunaga, C; Yamaoka, K
Abstract : It is well known that an interaction exists between smoking and exposure to asbestos in the occurrence of lung cancer, whereas occurrence of malignant mesothelioma has not been related to smoking. In the case of pleural thickening related to asbestos, there is a disagreement in previous studies as to the effect of smoking. This could be because the diagnosis of pleural changes has a subjective element. Taking this into account, in the present work the maximum width of the pleura was used as an index of pleural changes. Study subjects were 134 asbestos workers of a brake manufacturing company who had received medical checks in 1978 and in 1990. The maximum width of the pleura on the chest x ray films of the workers was measured by two examiners who did not know the year of examination or smoking state of the worker. A general linear model was applied to analyse the effects of smoking, the year of examination, age, and duration of exposure to asbestos. The difference between maximum widths measured in 1978 and 1990 suggested chronological progression. The increase in width during the 12 years, however, did not differ significantly between smokers and nonsmokers. This suggests that smoking does not significantly increase pleural thickening in asbestos workers.